Factor XI Deficiency Protects Against Atherogenesis in Apolipoprotein E/Factor XI Double Knockout Mice. Issue 3 (March 2016) - Shnerb Ganor, Reut; Harats, Dror; Schiby, Ginette; Gailani, David; Levkovitz, Hanna; Avivi, Camila; Tamarin, Ilia; Shaish, Aviv; Salomon, Ophira
Abstract : Objective—: Atherosclerosis and atherothrombosis are still major causes of mortality in the Western world, even after the widespread use of cholesterol-lowering medications. Recently, an association between local thrombin generation and atherosclerotic burden has been reported. Here, we studied the role of factor XI (FXI) deficiency in the process of atherosclerosis in mice. Approach and Results—: Apolipoprotein E/FXI double knockout mice, created for the first time in our laboratory. There was no difference in cholesterol levels or lipoprotein profiles between apolipoprotein E knockout and double knockout mice. Nevertheless, in 24-week-old double knockout mice, the atherosclerotic lesion area in the aortic sinus was reduced by 32% ( P =0.004) in comparison with apolipoprotein E knockout mice. In 42-week-old double knockout mice, FXI deficiency inhibited atherosclerosis progression significantly in the aortic sinus (25% reduction, P =0.024) and in the aortic arch (49% reduction, P =0.028), with a prominent reduction of macrophage infiltration in the atherosclerotic lesions. Conclusions—: FXI deprivation was shown to slow down atherogenesis in mice. The results suggest that the development of atherosclerosis can be prevented by targeting FXI. Abstract : Supplemental Digital Content is available in the text.